Causes of severe visual impairment and blindness in children in schools for the blind in Ethiopia. Issue 5 (1st May 2003) - Kello, A B; Gilbert, C
Abstract : Aims: To determine the causes of severe visual impairment and blindness in children in schools for the blind in Ethiopia, to aid in planning for the prevention and management of avoidable causes. Methods: Children attending three schools for the blind in Ethiopia were examined during April and May 2001 using the standard WHO/PBL eye examination record for children with blindness and low vision protocol. Data were analysed for those children aged less than 16 years using the epi-info -6 programme. Results: Among 360 pupils examined, 312 (96.7%) were aged <16 years. Of these children, 295 (94.5%) were blind or severely visually impaired. The major anatomical site of visual loss was cornea/phthisis (62.4%), followed by optic nerve lesions (9.8%), cataract/aphakia (9.2%), and lesions of the uvea (8.8%). The major aetiology was childhood factors (49.8%). The aetiology was unknown in 45.1% of cases. 68% of cases were considered to be potentially avoidable. Conclusions: Vitamin A deficiency and measles were the major causes of severe visual impairment/blindness in children in schools for the blind in Ethiopia. The majority of causes acquired during childhood could be avoided through provision of basic primary healthcare services.